2013
DOI: 10.1002/chem.201204281
|View full text |Cite
|
Sign up to set email alerts
|

On the Entangled Growth of NaTaO3 Cubes and Na2Ti3O7 Wires in Sodium Hydroxide Solution

Abstract: The entangled growth of sodium titanate Na2Ti3O7 nanowires and sodium tantalate NaTaO3 cubes was investigated with electron microscopy, X-ray diffraction, and UV diffuse reflectance spectroscopy. Depending on the composition of the Ta2O5- and TiO2-particle-based powder mixtures, which served as educts, we observed different types of hybridization effects. These include the titanium-induced contraction of the NaTaO3 perovskite-type unit cell and the generation of electronic defect states in NaTaO3 that give ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the present case, we find an intensity ratio of I 001 / I 110 = 1.1. This rules out oriented crystal growth effects and is consistent with the entangled coexistence of different nanosheets …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In the present case, we find an intensity ratio of I 001 / I 110 = 1.1. This rules out oriented crystal growth effects and is consistent with the entangled coexistence of different nanosheets …”
Section: Resultssupporting
confidence: 82%
“…This rules out oriented crystal growth effects 42 and is consistent with the entangled coexistence of different nanosheets. 43 The reaction of MgO nanocubes and MgO cubes with water in the absence of convective motion was subjected to timedependent XRD measurements. Figure 5 plots the 2Θ region of the periclase (002) and brucite (011) reflections.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This produces high energy materials which, as a result of H 2 O vapor exposure, undergo spontaneous room temperature conversion into magnesium oxychloride bers. Via the detailed exploration of the key process parameters with regard to the formation of magnesium oxychloride bers we can also demonstrate the great potential of MgO nanocubes as a model system for the elucidation of growth of anisotropic nanostructures, 29 the associated heterogeneous chemistry and, ultimately, the evolution of resulting microstructures. An important aspect relates to the localization of these transformation processes, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier powder XRD and solid state 29 Si MAS NMR studies revealed that the LTA sample consists of MgO nanocubes that are covered with surface adsorbed chlorosiloxane species Si x -Cl y O z . 14 Despite their pronounced reactivity in the ambient, the chemical composition as well the nano-/microstructure of this metastable composite can be retained over weeks of storage in vacuum.…”
Section: Surface Functionalization Of Mgo Particlesmentioning
confidence: 99%